Relationship between inquiry-based learning and students’ attitudes towards chemistry - Christine Mueni Nzomo; Peter Rugano; John Mungai Njoroge (International Journal of Evaluation and Research in Education (IJERE), 2023)
Students’ attitudes towards science subjects and especially chemistry have been attributed to the use of inquiry-based learning (IBL). The students’ attitudes are important predictors of academic achievement. The consistently poor performance in chemistry among secondary school students has been an issue of concern. This study sought to establish whether IBL has been used in the teaching of chemistry and if it had any influence on students’ attitudes towards chemistry. The study employed a correlational research design that involved conducting a survey of 21 teachers who were purposively selected, and 357 students selected through simple random sampling from the 21 classrooms that these teachers taught. The results revealed that teachers used IBL once a week (M=4.062) and students had positive attitudes towards chemistry (M=3.945). Besides, there was a significant association between IBL and the attitudes of students towards chemistry (r=0.997, p<0.05, R²=0.994).